Towards a sustainable blue economy: An evaluation of Indonesia's post-production non-tax state revenue policy using Dunn’s criteria - Arkan, Muhammad Farrel; Rosdiana, Haula (Social, Ecology, Economy for Sustainable Development Goals Journal, 2025)
Background: The Government of Indonesia has regulated the Non-Tax State Revenue (PNBP PHP) policy in relation to the vision of developing a blue economy-based capture fisheries sector. The policy aims to make a substantial transformation in the fiscal policy landscape. This study attempts to evaluate the PNBP Post-Production policy using Dunn's three policy evaluation criteria. Methods: In relation to these objectives, the researcher uses a post-positivist approach to obtain research results. Data collection was conducted through qualitative methods with several stages, namely in-depth interviews, field observations, and literature studies. Findings: The results show that the Post-Production PNBP policy can provide benefits for payers and tax authorities because PNBP is levied on the weight of real catches, not on estimates as regulated by Pre-Production PNBP. However, the PNBP policy does not meet Dunn's three criteria related to effectiveness, efficiency, and fairness. Based on the efficiency criterion, the policy is burdensome for payers and tax authorities. PNBP policy when viewed from the criteria of justice has fulfilled the benefit receive principle. However, the tariff index has not fulfilled the principle of nondiscrimination due to the differentiation of tariffs between vessel sizes which is no longer relevant. Conclusion: The government needs to further evaluate the policy of the Non-Tax State Revenue Policy for Collection of Fishery Products (PNBP PHP) in order to support the development of the capture fisheries sector based on the blue economy, at least the Post-Production PNBP policy must fulfill the three Dunn criteria. Novelty/Originality of this article: This research suggests the adoption of technology in each port that can meet the criteria of policy effectiveness and efficiency. In addition, it is necessary to reformulate the tariff index to meet the criteria of fairness.